2006
DOI: 10.4049/jimmunol.176.11.6918
|View full text |Cite
|
Sign up to set email alerts
|

F4/80+ Alternatively Activated Macrophages Control CD4+ T Cell Hyporesponsiveness at Sites Peripheral to Filarial Infection

Abstract: Both T cells and APC have been strongly implicated in the immune suppression observed during filarial nematode infections, but their relative roles are poorly understood, particularly in regard to timing and locality of action. Using Litomosoides sigmodontis infection of susceptible BALB/c mice, we have studied the progression of filarial immunosuppression leading to patent infection with blood microfilaremia. Patent infection is associated with decreased immune responsiveness in the draining thoracic lymph no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 63 publications
2
98
0
2
Order By: Relevance
“…NeMΦs recruited to the peritoneum following implantation of Brugia malayi adult worms express arginase-1, Ym1, and FIZZ1/RELMα [10]. Similarly, recent studies of Litomosoides sigmodontis infection showed recruitment of argininase-1-expressing F4/80 + macrophages [23]. In the strictly enteric H. polygyrus infection, during memory, but not primary, responses, AAMΦs accumulate at sites of larval invasion in the submucosa as early as four days after inoculation.…”
Section: Alternative Activation Of Macrophagesmentioning
confidence: 92%
See 2 more Smart Citations
“…NeMΦs recruited to the peritoneum following implantation of Brugia malayi adult worms express arginase-1, Ym1, and FIZZ1/RELMα [10]. Similarly, recent studies of Litomosoides sigmodontis infection showed recruitment of argininase-1-expressing F4/80 + macrophages [23]. In the strictly enteric H. polygyrus infection, during memory, but not primary, responses, AAMΦs accumulate at sites of larval invasion in the submucosa as early as four days after inoculation.…”
Section: Alternative Activation Of Macrophagesmentioning
confidence: 92%
“…In the memory Th2-type response to H. polygyrus, in vivo depletion of macrophages with chlodronate liposomes had no effect on the potent Th2-type cytokine response [3]. Furthermore, following L. sigmodontis infection, although AAMΦs could inhibit T cell proliferation in vitro, little effect on Th2-cell IL-4 and IL-5 was observed [23].…”
Section: Control Of Inflammationmentioning
confidence: 96%
See 1 more Smart Citation
“…By showing that B. malayi induces Foxp3 within the T cell population even in the absence of IL-4R signaling, we have established that this process is independent of alternatively activated macrophages. In long-term L. sigmodontis infections, alternatively activated macrophages are found together with both Foxp3 ϩ Tregs and CTLA-4 ϩ anergic effector T cells (39), although the interdependency of these populations has not been established. In our short-term experimental system, CTLA-4 remained high on Foxp3 Ϫ effector cells even in the IL-4R Ϫ/Ϫ setting, whereas CD4 ϩ FoxP3 ϩ cell expression of CD25, CD103, and CTLA-4, were indistinguishable from wild-type (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively activated macrophages are linked to the suppression of T cell responsiveness in chronic infections 22 and are important for down regulation of Th2 mediated immune pathology. In the present study, macrophage depletion did not change either Th1 (IFN-γ) or Th2 (IL-4, IL-13) cytokine expression, suggesting that macrophages are not involved in the initiation of the cytokine response elicited by N. brasiliensis infection, but are part of the downstream events in response to increased Th2 cytokine production.…”
Section: Discussionmentioning
confidence: 99%